ADVANCING THE METHODOLOGY FOR CULTIVATING MEDIA COMPETENCE AMONG FUTURE HEALTHCARE PROFESSIONALS - Yunusov Ilhomjon Yusupovich (Лучшие интеллектуальные исследования, 2024)
Abstract: In today's digital age, media competence has become essential for healthcare professionals to navigate the complex landscape of information dissemination, patient education, and professional communication. This article explores innovative methodologies aimed at enhancing the development of media competence among future doctors. Drawing upon theoretical frameworks and empirical research, we discuss strategies for integrating media literacy, digital communication skills, and ethical considerations into medical education curricula. By fostering critical thinking, creativity, and responsible use of media platforms, educators can empower medical students to effectively engage with diverse audiences and leverage media technologies to improve healthcare outcomes.